Key parameters of textured silicon solar cells of 26.6% photoconversion efficiency - Sachenko, A.V.; Kostylyov, V.P.; Korkishko, R.M.; Vlasyuk, V.M.; Sokolovskyi, I.O.; Dvernikov, B.F.; Chernenko, V.V.; Evstigneev, M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2021)
A new approach to modeling the parameters of high-efficiency textured silicon solar cells (SCs) has been presented. Unlike conventional optimization formalisms, our approach additionally includes such important factors as the non-radiative Auger recombination of excitons via deep impurity levels, as well as electron-hole pair recombination in the space charge region. A simple phenomenological expression offered by us earlier for the external quantum efficiency of the textured silicon solar cells with account of the photocurrent in the long-wave part of the absorption spectrum has also been used. Applying this approach, the key parameters of textured silicon SCs, namely: short-circuit current, open-circuit voltage, and photoconversion efficiency, have been theoretically determined. The proposed formalism allows calculating the thickness dependence of photoconversion efficiency, which is in good agreement with the experimental results obtained for the heterojunction SCs with the record photoconversion efficiency of 26.6%. The offered approach and the results of applying this phenomenological expression for the external quantum efficiency of the photocurrent in the long-wave part of the absorption spectrum can be used to optimize the characteristics of high-efficiency textured SCs based on monocrystalline silicon. Представлено новий підхід до моделювання параметрів високоефективних текстурованих кремнієвих сонячних елементів. На відміну від інших алгоритмів оптимізації, наш підхід додатково включає такі важливі чинники, як безвипромінювальна оже-рекомбінація екситонів крізь глибокі домішкові рівні, а також рекомбінація електронно-діркових пар в області просторового заряду. Також використовується простий феноменологічний вираз, який ми запропонували для зовнішньої квантової ефективності текстурованого кремнієвого сонячного елемента в довгохвильовій частині спектра поглинання. За допомогою цього підходу теоретично визначаються такі ключові параметри текстурованих кремнієвих сонячних елементів, як струм короткого замикання, напруга розімкнутого кола та ефективність фотоперетворення. Запропонований підхід дозволяє розрахувати залежність ефективності фотоперетворення від товщини, що добре узгоджується з експериментальними результатами, отриманими для гетероперехідних сонячних елементів з рекордною ефективністю фотоперетворення 26,6%. Запропонований підхід може бути використаний для оптимізації характеристик високоефективних текстурованих сонячних елементів на основі монокристалічного кремнію.